Continuous network of CNTs in poly(vinylidene fluoride) composites with high thermal and mechanical performance for heat exchangers. (22nd March 2019) - Cao, Min; Du, Chunyu; Guo, Hong; Song, Shasha; Li, Xipeng; Li, Baoan
Abstract: Polymeric materials with high thermal conductivity have drawn much attention in academic and industrial field recently. Due to poor dispersion and insufficient interconnection of fillers, traditional polymer composites present not only undesirable thermal conductivity but other declined properties even with high loaded thermal conductive nanofillers. In this work, the uniform and continuous network of (3-Aminopropyl)trimethoxysilane (APTMS) modified carbon nanotubes (A-CNTs) in poly(vinylidene fluoride) (PVDF) was built up by using the simple casting method. Thermal conductivity of 2.15 Wm −1 K −1 and tensile strength enhancement of 70% are achieved at 40 vol% A-CNTs loading compared with that of pure PVDF. The A-CNTs/PVDF composites exhibit an intensified thermal stability and sharply increased crystallinity (45.7%) compared with pure PVDF (28.5%). Moreover, for practical heat exchange experiment, the PVDF composites possess high heat transfer efficiency and long-last stability in corrosive water, which leads to the use of PVDF materials to supersede metal materials in heat transfers.